Three pseudo-components kinetic modeling and nonlinear dynamic optimization of Rhus Typhina pyrolysis with the distributed activation energy model. (5th July 2019) - Liu, Hui; Ahmad, Muhammad Sajjad; Alhumade, Hesham; Elkamel, Ali; Cattolica, Robert J.
Highlights: Rhus Typhina has great potentials as a biofuel with high volatile content and HHV. Three pseudo-components DAEM provides more details than isoconversional methods. The optimization model integrated with the DAEM improves the model accuracy. The standard deviation has big impact on the modeling of biomass pyrolysis. Abstract: In this work, a model using the Friedman method was applied to describe thermal decomposition of a biomass sample, Rhus Typhina (RT). The kinetic parameters such as activation energy and pre-exponential factor were achieved from this method. To provide more detailed description of biomass pyrolysis, a three pseudo-components distributed activation energy model (DAEM) was developed. In this DAEM model, a probability density function (PDF), the normal distribution function, was utilized to describe the distribution of activation energies for chemical reactions during pyrolysis. More importantly, three pseudo-components were proposed to represent hemicellulose, cellulose, and lignin & others. The three pseudo-components DAEM model was employed to predict biomass conversion and thermal decomposition rates. Moreover, a nonlinear dynamic optimization model was built and integrated with the DAEM to achieve better model-fitting. The model predictions were compared and validated with 3 sets of experiment data. Case studies were also conducted to investigate the impact of the PDF on thermal decomposition of hemicellulose, cellulose, and lignin.